Securitisation or Autocratisation? Hong Kong’s Rule of Law under the Shadow of China’ Authoritarian Governance - Lai, Yan-ho (Sage, 2023)
This article examines the nature of the legal system in Hong Kong and its process of autocratisation under the Chinese sovereign. This article suggests that, in colonial and post-colonial times, Hong Kong’s legal system follows the global trend of autocratic legalism that empowers the executive branch to use laws and courts to achieve the government’s political goals. With the recent imposition of the national security law, the political and legal systems of Hong Kong are further autocratised beneath the veil of securitisation, facilitating China’s authoritarian governance in Hong Kong.